Mapping the multi-step mechanism of a photoredox catalyzed atom-transfer radical polymerization reaction by direct observation of the reactive intermediates. Issue 17 (21st April 2020) - Lewis-Borrell, Luke; Sneha, Mahima; Bhattacherjee, Aditi; Clark, Ian P.; Orr-Ewing, Andrew J.
Abstract : Short-lived intermediates are tracked in real-time by transient absorption spectroscopy during a multi-step photoredox catalysed polymerization reaction. Abstract : The rapid development of new applications of photoredox catalysis has so far outpaced the mechanistic studies important for rational design of new classes of catalysts. Here, we report the use of ultrafast transient absorption spectroscopic methods to reveal both mechanistic and kinetic details of multiple sequential steps involved in an organocatalyzed atom transfer radical polymerization reaction. The polymerization system studied involves a N, N -diaryl dihydrophenazine photocatalyst, a radical initiator (methyl 2-bromopropionate) and a monomer (isoprene). Time-resolved spectroscopic measurements spanning sub-picosecond to microseconds ( i.e., almost 8 orders of magnitude of time) track the formation and loss of key reactive intermediates. These measurements identify both the excited state of the photocatalyst responsible for electron transfer and the radical intermediates participating in propagation reactions, as well as quantifying their lifetimes. The outcomes connect the properties of N, N -diaryl dihydrophenazine organic photocatalysts with the rates of sequential steps in the catalytic cycle.